2021
DOI: 10.1002/fsn3.2638
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and protective effects of extra virgin olive oil incorporated with diallyl sulfide against CCl4‐induced acute liver injury in mice

Abstract: Thepresentstudydelineatestheeffectsofincorporationof1%diallylsulfide(DAS)into extra virgin olive oil (EVOO) on the physico-chemical characteristics, in vitro antioxidant, and in vivo hepatoprotective properties in CCl 4 -induced acute liver injury inmice.ResultsshowedthattheDAS-richEVOOexhibitedgoodoxidativestability over one-month storage and preserved its original quality-related parameters including major components (oleic acid, linoleic acid, and palmitic acid), and minor components (tocopherols, chlorophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 54 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, it has been shown to be effective in preventing osteoporosis, as reported by (García-Gavilán et al, 2018). Additionally, the hepatoprotective and anti-inflammatory benefits have been observed in intoxicated mice which is attributed to the antioxidant activity of olive oil (Habibi et al, 2021).…”
Section: Demonstrated How Pbmentioning
confidence: 78%
“…Furthermore, it has been shown to be effective in preventing osteoporosis, as reported by (García-Gavilán et al, 2018). Additionally, the hepatoprotective and anti-inflammatory benefits have been observed in intoxicated mice which is attributed to the antioxidant activity of olive oil (Habibi et al, 2021).…”
Section: Demonstrated How Pbmentioning
confidence: 78%
“…HT helps to avoid liver steatosis and the mitochondrial dysfunction that comes with it, both of which are caused by [145] [146]…”
Section: Mufas Can Potentially Inhibit Tumor Growth and Proliferationmentioning
confidence: 99%
“…These mechanisms have been shown to effectively mitigate cellular damage ( Ajibade et al, 2022 ; Caporali et al, 2022 ). Previous research has demonstrated that Lut exhibits the potential to mitigate the presence of inflammatory mediators through the elimination of free radicals, thereby offering therapeutic benefits in the treatment of carbon tetrachloride ( Habibi et al, 2021 ), mercury ( Tan et al, 2018 ), arsenic ( Quiller et al, 2018 ), and lead ( Baty et al, 2020 ) poisoning. Additionally, Lut has been shown to enhance energy supply and exert a protective role ( Zhang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%